A systemic history of the Middle Way: its biological, psycho-developmental, and cultural conditions - Ellis, Robert M. (Middle way philosophy, 2024)
"This book examines the history of the Middle Way in four inter-related ways: as the biological development of organisms in relation to reinforcing or balancing feedback loops, as the psychological development of individual humans during a lifetime, as a succession of reinforcing and balancing feedback tendencies in human culture through history, and as a successive development of integrative practice. This shows how the Middle Way is a path distinctive to the human response to complexity, but nevertheless one rooted in the wider processes of all life. In the process it provides a detailed exploration of the relationship between the Middle Way and systems theory, biology, developmental psychology, and world history"